Crecimiento y desarrollo del cacao CCN -51 (Theobroma cacao L.) bajo niveles contrastantes de sombra y fertilización en Zamora Chinchipe - Campoverde Córdova, Rosa Carolina (2022)
Cacao (Theobroma cacao L.) is one of the leading products of agricultural excellence for export in Ecuador, however, despite its economic and agronomic relevance, the national average production yield does not exceed 0.5 t ha-1. 1, a problem related to the productivity system of this crop, which is primarily low technology, added to this, there is little knowledge about the factors that determine the production yield. Likewise, there is limited information on the effect of fertilization and the use of shade for cacao production in conditions of the Ecuadorian Amazon, therefore this research work aims to evaluate the different levels of fertilization and shade during the growth and development of the cacao clone CCN-51. In this study, the clone CCN-5 was used as plant material and an assay was established at the "El Padmi" Experimental Station, in the province of Zamora Chinchipe. Four treatments were evaluated: T1= Control (without shade and without fertilization), T2= Fertilization (0% shade and 100% fertilization), T3= Shade (use of mesh that prevents the passage of 80% of solar radiation), and T4= Shade - fertilization interaction (80% shade and 100% fertilization). Morphological variables such as crown diameter, trunk cross-sectional area (ASTT), and absolute and relative growth rate (TCA and TCR) were evaluated. In addition, physiological variables such as leaf area index (LAI), chlorophyll concentration in leaves and leaf stomatal density, and productive variables such as fruit length, estimated fruit weight, absolute growth rate, and relative growth rate were measured. In the soil, the pH and electrical conductivity were measured periodically. The effect of the silver treatments on the dependent variables was evaluated using ANOVA and Tukey's means test (p=0.05). It should be noted that no statistically significant effects were found in the treatments, but it was observed that fertilization increased the cross-sectional area of the trunk, the electrical conductivity, and the length of the fruit, as well as the estimated weight and estimated production per plant. not significantly, but slight changes could be evidenced. Likewise, the shade favored the foliar expansion, observing an increase in the foliar area of the plant, as well as in the LAI, crown diameter, stomatal density, as well as in length of the fruit, weight, and estimated yield per plant. The results of this work suggest that nutrition and the reduction of solar radiation of cacao can favor the growth of this crop from its early stages, however, it is necessary to continue with the study in the following stages of the crop to see the impact on the performance. Keywords: Theobroma cacao, fertilization, shading, growth, and development.